Rheumatoid Arthritis: A Rare Cause of Cardiac Tamponade - Yiğit ÇANGA,; Kazım Serhan ÖZCAN,; Mehmet Baran KARATAŞ,; Gündüz DURMUŞ,; İzzet Celal ERDİNLER, (Archives of Rheumatology, 2012)
Rheumatoid arthritis (RA) is a chronic multisystem disease of unknown cause which affects approximately 1% of the population. The typical characteristic of RA is persistent inflammatory synovitis which usually involves peripheral joints in a symmetric distribution. Systemic involvements of RA include pericarditis, pleuritis, vasculitis, entrapment neuropathy, interstitial lung disease and Sjogren and Felty syndromes. Echocardiographic and postmortem studies have shown that RA affects pericardium in nearly 50% of the patients. However, cardiac tamponade is a rare complication of RA. In this report, we present a surgically-treated 61-year-old female patient with cardiac tamponade secondary to loculated pericardial effusion.